Thermal Management Technology of New-generation High-voltage SiC Devices Applied in Rail Transit Traction System - Kai HE; Xingzhi WANG; En TIAN; Yanping CHEN; Zechun DOU (机车电传动)
The wide band-gap devices represented by SiC are becoming the research focus of power semiconductor devices. The new generation of high-voltage packaging is the main packaging form for high-power SiC devices to cope with high-voltage, heat dissipation and parallel use. In this paper, the key thermal performance parameters of the new generation of high-voltage packaging SiC devices, such as packaging structure characteristics, current density, dynamic and static loss parameters, thermal resistance, and junction temperature were compared with those of traditional Si based devices. Based on the typical static and dynamic conditions of traction system, the loss, junction temperature and temperature stress spectrum of the two types of devices under the same working conditions were comprehensively compared. The results showed that SiC devices have higher current carrying capacity and higher efficiency, but there are also some shortcomings, such as higher junction shell thermal resistance and interface thermal resistance, higher heat dissipation power density and lower allowable junction temperature. In practical application, it is necessary to consider circuit topology, current utilization, switching frequency and thermal management system to ensure that the advantages of SiC devices can be brought into full play.